Civil Liability Digital Platform Regarding Personal Data Leaks Following the Enactment of Law Number 27 of 2022 Concerning Personal Data Protection - Ulfanora; Nanda Utama (Jurnal Sakato Ekasakti Law Review, 2026)
The rapid development of technology has impacted various aspects of life, including economic, social, cultural, legal, and political aspects. This technological advancement has transformed the way people communicate and the provision of government services to the public. Information technology has become a new way for people to obtain information autonomously. Technology has become a Human Right to Digital Access. In general, the public is not yet aware of the impact of information misuse, resulting in low awareness of personal data protection. As a form of government concern for the public, who are both users and actors in this digital development, various regulations or rules have been established to provide legal protection for all people in utilizing the currently rapidly developing digital advancements. The existence of Law Number 27 of 2022 concerning Personal Data Protection is due to the numerous cases of data leaks in Indonesia. Research results explain thatFirst, Indonesia has ratified personal data protection regulations since 2022. The ratification of personal data protection regulations is effective starting from 2024. When Law Number 27 of 2022 concerning personal data protection was ratified into regulations and implemented in society, there were still shortcomings that became obstacles in its implementation in society.Second,. Following the enactment of Law Number 27 of 2022 concerning Personal Data Protection, the civil liability of digital platforms has provided legal certainty. Law Number 27 of 2022 concerning Personal Data Protection explicitly places the burden of responsibility on them as data controllers. If a leak occurs due to a security system failure, they can no longer avoid legal responsibility to compensate for the losses you have suffered as a data subject.